PENGARUH PARTISIPASI PENGANGGARAN, ASIMETRI INFORMASI DAN BUDAYA ORGANISASI PADA SENJANGAN ANGGARAN (STUDI KASUS PADA KOPERASI DI KOTA MALANG) - Mufarrihah Mufarrihah (e_Jurnal Ilmiah Riset Akuntansi, 2017)
This research aims to know the influence of participation in budgeting, information asymmetry, and organizational culture in thebudgetary slackin cooperative city of Malang. To be able to achieve that goal used linear regression data analysis techniques double, F-test and t-test. Methods of collecting data in this study using a questionnaire that was distributed to the Manager, Secretary and Treasurer at the cooperative in the city of Malang. Based on the results of analysis of the mind that simultaneously (a) variable budget participation, information asymmetry and organizational culture significantly to budgetary slack, partially variable and (b) the budget participation of a significant negative effect on budgetary slack cooperative in Malang (c) asymmetry of information of significant positive effect on the budgetary slack cooperative in Malang and (d) organizational culture positive significant effect on budgetary slack cooperative in Malang.